Exploring Sources of Gravity Waves in the Southern Winter Stratosphere Using 3‐D Satellite Observations and Backward Ray‐Tracing - Noble, Phoebe E.; Rhode, Sebastian; Hindley, Neil P.; Berthelemy, Peter; Moffat-Griffin, Tracy; Preusse, Peter; Hoffmann, Lars; Wright, Corwin J. (Wiley, 2024)
During austral winter, the southern high latitudes has some of the most intense stratospheric gravity wave (GW) activity globally. However, producing accurate representations of GW dynamics in this region in numerical models has proved exceptionally challenging. One reason for this is that questions remain regarding the relative contributions of orographic and non-orographic sources of GWs here. We use three-dimensional (3-D) satellite GW observations from the Atmospheric Infrared Sounder in austral winter 2012 in combination with the Gravity-wave Regional Or Global Ray Tracer to backward trace GW rays to their sources. We trace over 14.2 million rays, through ERA5 reanalysis background atmosphere, to their lower atmospheric sources. We find that GWs observed thousands of km downstream can be traced back to key orographic regions, and that on average, all waves (orographic and non-orographic) converge meridionally over the Southern Ocean. We estimate that across this winter, orographic sources contribute around 5%–35% to the total momentum flux (MF) observed near 60S. The remaining proportion consists of waves from non-orographic sources, which although typically carry lower MF, the large spatial extent of non-orographic sources leads to a higher overall contribution. We also quantify the proportion of MF traced back to different regions across the whole southern high latitudes area in order to measure the relative importance of these different regions. These results provide the important insights needed to advance our knowledge of the atmospheric momentum budget in the southern high latitudes.